Exploring Sustainable Features in a 19th-Century Religious Building: The Case of Jami Mosque of Mentok, Bangka - Primayudha, Novrizal; Santosa, Imam; Syarief, Achmad; Destiarmand, Achmad Haldani; Primayudha, Novrizal Primayudha (EMARA: Indonesian Journal of Architecture, 2026)
Research on thermal performance and energy conservation in mosque architecture remains relatively limited compared to other building typologies. Meanwhile, sustainable architecture discourse in recent decades has been largely driven by technological advancements, often overlooking vernacular design practices that have long enabled local communities to adapt to their environmental conditions. This study addresses this gap by examining how traditional mosque architecture embodies sustainable principles through context-responsive design strategies. This study focuses on  Jami Mosque of Mentok, a 19th-century mosque located in the tin-mining town of Bangka, Indonesia. Using a qualitative approach through field observations and in-depth interviews, the study finds that the mosque integrates passive design strategies such as natural ventilation, high ceilings supported by wooden pillars, strategically positioned openings, and optimised daylighting. These design features reflect the local community’s understanding of the coastal climate, making the building both functional and environmentally responsive. The findings indicate that  Jami Mosque of Mentok functions not only as a place of worship and a symbol of Malay cultural identity, but also as a representation of vernacular architectural ingenuity that harmonises with its environmental and social context.